Men of blood : violence, manliness and criminal justice in Victorian England - Wiener, Martin J. (Cambridge University Press, 2004)
An examination of the treatment of serious violence by men against women in nineteenth-century England. During Victoria's reign the criminal law came to punish such violence more systematically and heavily, while propagating a new, more pacific ideal of manliness. Yet this apparently progressive legal development called forth strong resistance.